Influence of facilities on cow time budgets - Harner, Joseph P.; Smith, John F., 1962-; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A model was developed to evaluate the impact of facilities on cow time budgets. The model suggests that in inadequate facilities overcrowding of the facility by 25% or more resulted because occupancy rate exceeded 100%. The model also is useful in evaluating the impact of time at milking center and milk-ing frequency on cow time budget. In general, the first groups of cows through the milking parlor will have adequate time for resting, feeding, socializing, and watering. The last groups of cows through the parlor, however, do not have adequate time for these activities if the time at the milking center at each milk-ing is 2 or more hours. Reducing time at the milking center is critical when milking 3 times daily to ensure that the last groups of cows through the parlor have adequate time for normal behavioral activities once back in the housing area.
Dairy Research, 2006 is known as Dairy Day, 2006
Keywords: Dairy; Facilities; Feedline; Freestalls; Time